If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x * x(3 + -4x) = 4x(3 + -4x) Multiply x * x x2 * x(3 + -4x) = 4x(3 + -4x) Multiply x2 * x x3(3 + -4x) = 4x(3 + -4x) (3 * x3 + -4x * x3) = 4x(3 + -4x) (3x3 + -4x4) = 4x(3 + -4x) 3x3 + -4x4 = (3 * 4x + -4x * 4x) 3x3 + -4x4 = (12x + -16x2) Solving 3x3 + -4x4 = 12x + -16x2 Solving for variable 'x'. Reorder the terms: -12x + 16x2 + 3x3 + -4x4 = 12x + -16x2 + -12x + 16x2 Reorder the terms: -12x + 16x2 + 3x3 + -4x4 = 12x + -12x + -16x2 + 16x2 Combine like terms: 12x + -12x = 0 -12x + 16x2 + 3x3 + -4x4 = 0 + -16x2 + 16x2 -12x + 16x2 + 3x3 + -4x4 = -16x2 + 16x2 Combine like terms: -16x2 + 16x2 = 0 -12x + 16x2 + 3x3 + -4x4 = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-12 + 16x + 3x2 + -4x3) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-12 + 16x + 3x2 + -4x3)' equal to zero and attempt to solve: Simplifying -12 + 16x + 3x2 + -4x3 = 0 Solving -12 + 16x + 3x2 + -4x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| x-1388=-15 | | x-745=-14 | | x(3-4x)=4x(3-4x) | | x-1450=734 | | .333p-.375p=3 | | x+235=-200 | | .333p-.375p=5 | | (8x^2-4x+6)(5x+5)= | | 1p-8p=5 | | -1/3=-3/2 | | (5x^2-2x-5)(3x+9)= | | x-32=-15 | | -7c+9=c-1 | | 17c+9=c-1 | | x+30=-15 | | x-128=-132 | | x+28=-15 | | 18+(5*73)+7*(7+23)= | | x+27=35 | | .75x=50000 | | 3p-10=23 | | 5x-7=21 | | x+23=-15 | | 11a+2b= | | 2x-7+8x-3=4x+6x+10 | | -8y+6=-9-7y | | x-48=6 | | 5(x+2)-(5x+10)=0 | | 4x+2=10x-1 | | 80*6x=45+32*4x+23x | | (3x+1)(2x-4)-x(6x-7)=0 | | 32=48t+16t^2 |